2018
DOI: 10.1055/s-0038-1660811
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Wrist Patterns Founded on Measurements in Plain Radiographs

Abstract: Background In joints, structure dictates function and consequently pathology. Interpreting wrist structure is complicated by the existence of multiple joints and variability in bone shapes and anatomical patterns in the wrist. Previous studies evaluated lunate and capitate shape in the midcarpal joint, and two distinct patterns have been identified. Purpose Our purpose was to further characterize the two wrist patterns in normal wrist radiographs using measurements of joint contact and position. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These significantly included the length of capitate circumference in contact with the lunate and nearly significantly the percentage of capitate circumference in contact with the lunate. In a previous study, 21 the authors found a higher percentage of capitate circumference in contact with the lunate in type 1 wrists. No correlations were found with the measurements distal to the distal carpal row (trapezium and carpometacarpal row).…”
Section: Discussionmentioning
confidence: 73%
“…These significantly included the length of capitate circumference in contact with the lunate and nearly significantly the percentage of capitate circumference in contact with the lunate. In a previous study, 21 the authors found a higher percentage of capitate circumference in contact with the lunate in type 1 wrists. No correlations were found with the measurements distal to the distal carpal row (trapezium and carpometacarpal row).…”
Section: Discussionmentioning
confidence: 73%
“…• Percent (capitate circumference) that articulates with the base of the index and middle and ring metacarpal bones is measured. The measurements were based on previous studies 4,8 The second part consists of generating a 3D model of the wrist midcarpal joint using finite element analysis, as follows.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The structure of the midcarpal joint has been divided into two structural patterns: a type 1 wrist that has a lunate type 1 and spherical proximal capitate, and a type 2 wrist with a type 2 lunate and flat proximal capitate. 4,5 This variation has been shown to affect load transfer in between the ulna and radius. 6 Assuming that these structural disparities will affect load transfer through the midcarpal joint, the purpose of this study was to:…”
Section: Introductionmentioning
confidence: 99%